Hybrid intelligence : merging collective and artificial intelligence to solve complex problems - Holt, Kevin (Strategic planner) (Routledge, 2026)
Uniquely aimed at teams that think together to solve problems and make decisions, this book explains how to enhance the collective intelligence of a team-size group and combine it with the artificial intelligence (AI) of generative AI to create a hybrid intelligence that is smarter than either one on its own.Boards, committees, and other team-size groups of 5-20 people are the primary problem-solving and decision-making units within organizations, and they form the bridges between organizations, industries, and nations that collaborate on projects. So how can leaders exponentially improve their teams' capabilities? Assemble the right people, arm them with the right processes, and execute those processes on the right platforms-then add generative AI to enhance those practices. This book describes and synthesizes various ways of increasing a group's collective intelligence through people, process, and platform practices, and goes on to explain how to augment the practices with generative AI, including how to ask it questions and what questions to ask to obtain superior answers. The resulting upsurge in team capability enables organizations to survive and thrive in a world that is growing progressively more competitive and complex.This book will become the definitive resource for leaders and managers of commercial, government, and nonprofit organizations who want to learn how to significantly improve their teams' problem-solving and decision-making ability by increasing their collective intelligence and combining it with the artificial intelligence of generative AI.
Keywords: Group problem solving.; Swarm intelligence.; Artificial intelligence.; elektronické knihy; electronic books